Biosensing: Graphene Field‐Effect Transistors for the Sensitive and Selective Detection of Escherichia coli Using Pyrene‐Tagged DNA Aptamer (Adv. Healthcare Mater. 19/2017). Issue 19 (11th October 2017) - Wu, Guangfu; Dai, Ziwen; Tang, Xin; Lin, Zihong; Lo, Pik Kwan; Meyyappan, M.; Lai, King Wai Chiu
Abstract : An aptamer modified graphene field‐effect transistor (G‐FET) based biosensor for electrical detection of E. coli is developed by King Wai Chiu Lai and co‐workers in article number1700736 . The change of the carrier density in graphene due to the attachment of E. coli is correlated with the electrical response of the graphene biosensors. The electrical response is analyzed and optimized by tuning the gate voltage which affects the carrier mobility of graphene. The excellent sensing performance (high sensitivity, selectivity and stability) opens up the possibility to utilize aptamer modified graphene device for pathogens detection in food and water quality monitoring and early diagnosis of pathogen infections.